Community Political Advocacy in the Farmers’ Market from Barranca, Puntarenas, Costa Rica, in 2023 - Bolaños Alvarado, Bayron (2024)
This article presents a case study on the citizen participation strategies implemented by farmers from Barranca, Puntarenas, during 2023, to resolve the conflict stemming from the eviction of their Farmers’ Market in 2020. The closure of this commercial space had serious negative economic and social consequences for producers and the community. The analysis of the political and legislative process helped us identify the strategies used by farmers to actively engage in finding a viable solution to the problem. These tactics included presenting a bill in the Legislative Assembly and exerting constant pressure on deputies, which resulted in the approval of the legislation that facilitated the return of the farmers’ market to the original facilities. The study assessed the effectiveness of these context-specific participatory strategies in influencing concrete results. Findings offer valuable lessons on localized ways of citizen participation in the formal political sphere, aiming to promote more inclusive democracies geared towards collective well-being.